COMPARISON OF ILEAL CONDUIT AND TUUC: A 4 YEARS STUDY - Soerohardjo, Indrawarman; Zulfiqqar, Andy; Yuri, Prahara; Hendri, Ahmad Z. (Indonesian Journal of Urology, 2022)
Objective: This study aims to compare 4 years of experience of IC and TUUC in the same period and among similar experienced surgeons. Material & Methods: Between January 2016 and August 2019, 44 radical cystectomies were performed, but 4 patients were excluded due to incomplete data or who underwent neo-bladder procedures. The primary endpoint was 30 days of complication rate and intraoperative complications. Bowel movement, ambulation, and length of stay (LOS) postoperatively were followed-up over a period of 30-day postoperatively. Results: 12 male patients underwent TUUC and 24 male patients IC, while only 4 female patients underwent IC. The mean of LOS of IC was 12.72 8.6 and 10.08 3.5 for TUUC; there were no significant differences between arms. However, TUUC had lower intra-operatively bleeding (779.17 441.15 ml) compared to IC (1328.57 810.40 ml). There was no difference in early complications between arms. Conclusion: Our results suggest that TUU with UC diversion may be used as a viable option of urinary diversion in radical cystectomy. This technique provides similar safety both surgically and oncologically.